2009
DOI: 10.1073/pnas.0806761106
|View full text |Cite
|
Sign up to set email alerts
|

Thinking like a trader selectively reduces individuals' loss aversion

Abstract: Research on emotion regulation has focused upon observers' ability to regulate their emotional reaction to stimuli such as affective pictures, but many other aspects of our affective experience are also potentially amenable to intentional cognitive regulation. In the domain of decision-making, recent work has demonstrated a role for emotions in choice, although such work has generally remained agnostic about the specific role of emotion. Combining psychologically-derived cognitive strategies, physiological mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
431
3
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 401 publications
(515 citation statements)
references
References 53 publications
(49 reference statements)
49
431
3
3
Order By: Relevance
“…A parent's job loss can also reduce the health of subsequently born children (Lindo 2011). Hessner et al 2009), which has been cited as a potential source of friction in the labor market (Katz 2010). 3 In this study I consider bad news about mass layoffs and plant closings in light of the human capital literature which studies the damaging effects of stress experienced by women during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…A parent's job loss can also reduce the health of subsequently born children (Lindo 2011). Hessner et al 2009), which has been cited as a potential source of friction in the labor market (Katz 2010). 3 In this study I consider bad news about mass layoffs and plant closings in light of the human capital literature which studies the damaging effects of stress experienced by women during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…18 Jap [27], in field interviews with suppliers participating in reverse auctions, found that the compressed time frame of open-bid auctions creates a stressful context for the supplier and many suppliers complained that the format prevented them from carefully considering price bids and gave them a sense of being out of control. 19 Wood and Schweitzer [28] in their experiments induced different levels of anxiety (high vs. low) and found negotiators experiencing high levels of anxiety make steeper concessions and exit bargaining situations earlier. …”
Section: Discussionmentioning
confidence: 97%
“…The decision to wait means another decision in the next period, and this might have come at a psychological cost such as stress or anxiety, resulting in the shorter delay in dynamic trials. 19 Anxious subjects could reasonably trade off profit from waiting longer for a reduction in anxiety by selling sooner than predicted by a no-anxiety benchmark. This hypothesis is also consistent with a substantial literature on preference for resolution of uncertainty in other areas of economics [29,30,31,32,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the main value of the model stems from making the real cost of false positives explicit. Reframing false positives as prospective gains makes termination decisions easier 11 . In reality, there are yet further costs that are associated with false positives.…”
Section: Discussionmentioning
confidence: 99%